2012
DOI: 10.4161/hv.20204
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage and uptake predictors among Spanish adults suffering COPD

Abstract: Abbreviations: chronic obstructive pulmonary disease, COPDThe aim of this study is to compare influenza vaccination coverage among Spaniards aged 40 y or over who suffer from chronic obstructive pulmonary disease (COPD) with those without this illness to identify the factors that influence vaccination uptake among patients with COPD.Data was extracted from the European Health Survey performed in Spain in 2009/10, and analyzed data on 15,355 Spaniards ($ 40 y of age), of whom 1,309 (8.2% 95% CI 7.7-8.7) had COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…160 This assumption was based on vaccination rates of 50% and between 80% and 93% reported in Spanish and UK studies. 161,162 The average number of days and cost of home oxygen therapy received in each severity group was derived from expert opinion reported in Hertel et al (2012). 140 Smoking-cessation advice and pulmonary rehabilitation are also recommended by NICE as usual care for COPD patients.…”
Section: Routine Health-care Visitsmentioning
confidence: 99%
“…160 This assumption was based on vaccination rates of 50% and between 80% and 93% reported in Spanish and UK studies. 161,162 The average number of days and cost of home oxygen therapy received in each severity group was derived from expert opinion reported in Hertel et al (2012). 140 Smoking-cessation advice and pulmonary rehabilitation are also recommended by NICE as usual care for COPD patients.…”
Section: Routine Health-care Visitsmentioning
confidence: 99%
“…The morbidity and mortality associated with influenza are high among the elderly, pregnant women, immunocompromised hosts, and those with chronic diseases such as diabetes mellitus (DM). [1][2][3] Diabetes is a serious and growing health problem worldwide. It is estimated that a total of 439 million adults will be affected by DM by 2030, with a 20% increase in developed countries and a 69% increase in developing countries from 2010 to 2030.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, an extensive review of the literature was carried out to identify the existing evidence on vaccination behavior. Previous studies have reported that people who are older [ 19 , 20 , 21 , 22 ], married [ 23 , 24 , 25 , 26 ], better educated [ 27 , 28 ], non-smokers [ 22 , 25 , 26 ], have chronic illnesses [ 16 ], no limitations on their activities [ 29 ], or who have medical insurance [ 29 ] are more likely to receive the vaccine than those without these characteristics. Conversely, research has shown that people who are allergic to medication [ 16 ] or smokers [ 30 ] are less likely to be vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…A scant few studies have been published on influenza vaccinations among Chinese populations. It should be noted that vaccination rates for people with CRD vary greatly, from 19.9% to 71% [ 16 , 22 , 23 , 24 , 25 , 28 ], still far behind the 2020 target to increase the percentage of high-risk adults to the rate of 90% that is common in developed countries [ 31 ].…”
Section: Introductionmentioning
confidence: 99%